UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MELALUI MEDIA VIDEO PEMBELAJARAN SUKU KATA PADA SISWA KELAS I SEKOLAH DASAR - Nurul Firli Chairunnisa; Arsyi Rizqia Amalia; Dyah Lyesmaya (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This study aims to explore the use of syllable learning video media in improving beginning reading skills in grade I students in elementary school. Beginning reading is an important stage in learning to read, where students learn to recognize letters, words, and understand the relationship between sound and writing. This study used classroom action research (PTK). The results showed that the use of learning video media can improve early reading skills, as evidenced by the results of measurements with observation sheets measuring student results in cycle, I obtained a score of 73% and cycle II increased to 86,5%.